GAMBARAN KARAKTERISTIK KEKURANGAN ENERGI KRONIK (KEK) PADA PASIEN IBU HAMIL BERDASARKAN KARTU 3E DI PUSKESMAS BELIMBING TAHUN 2023 - Tia Reza; Anwar Rohdatul Aisy (Nusantara Hasana Journal, 2025)
Chronic Energy Deficiency (CED) is one of the indirect causes of maternal mortality, where CED in mothers and infants has accounted for 11% of global disease in the world and at least 3.5 million deaths in Asia each year. Severity in pregnant women can be seen from the measurement of upper arm circumference (LILA) which is less than 23.5 cm. SEZ in pregnant women can be caused by an imbalance in nutritional intake between energy and protein that lasts for a long time (chronic) so that the nutrients needed by the body are not fulfilled. Risk factors for the occurrence of SEZ are nutrient intake, infectious diseases, age, parity, pregnancy distance, education, occupation, knowledge and family incomeThis study aims to determine the characteristics of chronic energy deficiency (CHD) in pregnant women patients based on the 3E card at the Belimbing Health Center in 2023. The type of research used is categorical descriptive research with a cross sectional design. The sampling technique uses a type of probability sampling sample which is a simple random sampling technique. The minimum sample in this study was 73 samples. The incidence of SEZ is most prevalent in non-risk age (20-35 years) as many as 68 cases (93.2%), Parity is multiparous as many as 55 cases (75.3%), the last education is secondary level as many as 43 cases (58.9%), and Employment is not working as many as 45 cases (61.6%). The incidence of SEZ in pregnant women mostly occurred at non-risk ages, namely 20-35 years, the incidence of SEZ in pregnant women mostly occurred in multiparous pregnancies, the incidence of SEZ pregnant women mostly with secondary level education (SMA, SMK and SLTA), and most of the incidence of SEZ occurred in pregnant women who did not work.